Board Performance and Preparation Interventions among the Teacher Education Graduates in Eastern Rizal - Fulgado, Julieta ST. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aimed to assess teacher education graduates' performance over five consecutive years against the national passing rate. It was noticed that the repeaters were outperformed by first-time BEED and BSE takers. Repeaters had contributed under the national passing-rate outcomes of the takers. The College of Education emphasized that when taking the BLEPT, the implementation of the Competency Building Course and the pre-board examination requirements contribute to their exposure.